2014
DOI: 10.1016/j.ydbio.2013.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Dual function of Yap in the regulation of lens progenitor cells and cellular polarity

Abstract: Hippo-Yap signaling has been implicated in organ size determination via its regulation of cell proliferation, growth and apoptosis (Pan, 2007). The vertebrate lens comprises only two major cell types, lens progenitors and differentiated fiber cells, thereby providing a relatively simple system for studying size-controlling mechanisms. In order to investigate the role of Hippo-Yap signaling in lens size regulation, we conditionally ablated Yap in the developing mouse lens. Lens progenitor specific deletion of Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 59 publications
(69 reference statements)
4
42
0
Order By: Relevance
“…Yap’s function in maintaining progenitor pools by promoting cell proliferation has been well demonstrated in many tissues, including cardiac and lens (Heallen et al, 2011; Song et al, 2014). In addition, overexpression of Yap enhanced proliferation of progenitors in postnatal retinal explants, and RNA interference decreased proliferation (Zhang et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Yap’s function in maintaining progenitor pools by promoting cell proliferation has been well demonstrated in many tissues, including cardiac and lens (Heallen et al, 2011; Song et al, 2014). In addition, overexpression of Yap enhanced proliferation of progenitors in postnatal retinal explants, and RNA interference decreased proliferation (Zhang et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Destabilized Crumbs polarity complex proteins and cell-cell junctions in Yap CKO are consistent with previous reports, including a comprehensive proteomics study showing significant overrepresentation of proteins associated with cell-cell contacts, among them apical polarity complex proteins, as interacting partners of Yap (Kohli et al, 2014; Varelas et al, 2010). Unstable cell-cell attachment and destabilization of apical polarity complex proteins were independently observed in developing ependymal cells and lens deficient in Yap (Park et al, 2016; Song et al, 2014). We also noted that Yap functions cell-autonomously within retinal epithelia (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, ablation of β-catenin does not cause lens herniation, but rather a disruption in polarity and adhesion of the lens epithelial cells, which are similar phenotypes to those observed in cadherin knockouts [119, 154, 201]. Genetic rescue experiments also demonstrated that the cadherin-binding protein NF2 negatively regulates YAP, which is required both to maintain lens epithelial cell polarity and to prevent premature differentiation [202, 203]. YAP has also been shown to be intricately involved in Wnt/β-catenin signaling in other systems.…”
Section: Reiterative Use Of the Same Genes And Signaling Pathways Dirmentioning
confidence: 93%